Values Education In Legal Treatment ff The Husband Over The Wife Nushuz - Qurrotul Ainiyah (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
This research raises the question of how Islam regulates the beatings of the husband against the wife of Nusyuz in the perspective of UUKDRT and Criminal Code in Indonesia which is then reviewed by the value of Islamic education. The type of research is bibliography. And the results of research states that Islam provides a rule for husbands to educate the wife who is rebelling to be a good wife, that is with 3 stages: advise, separate bed and hit him with no harm, imprint and not a dangerous place. The application of punishment for the nusyuz wife is an educational effort in order to restore the conditions in accordance with the initial purpose of the household, which must be applied prosfesianol and full responsibility.